Chronic partial colonic obstruction from a congenital web - Timothy Jumbi; Peter Mwika (Elsevier, 2020)
Congenital colonic stenosis is a rare anomaly that mostly presents in the neonatal period with colonic obstruction. The similarity of presentation with Hirschsprung diseases prompts discussion on suspicion, detection and management. We therefore present a case of a 1-year old girl with colonic stenosis initially thought to have Hirschsprung disease, with the aim of highlighting the role of clinical, radiological and histological assessment in management.